PENILAIAN EFEKTIFITAS PENGELOLAAN TAMAN WISATA ALAM LAUT (TWAL) TELUK KUPANG NUSA TENGGARA TIMUR - ROLINDA INNEKE FOENAY; N.K Mardani; Joko Wiryatno (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2011)
Damage to coral reef ecosystems in the Bay of Kupang reaching 30.6%. Activities to restore coral reefs are also conducted through coral transplantation programs. Although this activity was relatively successful, but the power of coral reefs to recover relatively longer, while coral mining and destructive fishing in the areas within the region is still on going. The purpose of this research is (1) to investigate the effectiveness and efficiency of management 1WAL Kupang Bay. (2) To investigate condition of coral reefs live in Kupang Bay after the management and (3) to investigate condition of socioeconomic the communities around Kupang Bay after the management. The method of research used observation and direct observation in the field, with socioeconomic data retrieval techniques using quesioner and coral reef data using Line Intercept 'Jransect (LI11 method and discovery of documents which contain about the development of coral cover. The results showed that the communities around Kupang Bay 1WA L not know and was not involved in the preparation of management plan 1WA L Kupang Bay. Data on coral reefs show that damage continues to occur with a marked decline in coral cover prosesntase. Following up on these circumstances will require collaborative management mechanism that involves the community as one of the stakeholders in the area of the bay 1WAL Kupang.